Triiodothyronine attenuates estradiol-induced increases in dopamine D-2 receptor number in rat anterior pituitary - Nedvídková, J; Pacák, K; Nedvídek, J; Goldstein, D S; Schreiber, V (Brain research, 1996)
Estrogens promote adenohypophyseal enlargement and tumor transformation, and thyroid hormones antagonize these effects. Hormone-induced pituitary enlargement may be mediated by alterations in pituitary dopaminergic function. The present study examined the effects of chronic (20 days) administration of estradiol benzoate (EB), triiodothyronine (T3), or EB and T3 (T3 + EB) on dopamine (D-2) receptors in rat anterior pituitary. D-2 receptor number increased after EB without altered receptor affinity. T3 alone did not affect D-2 receptor number in the anterior pituitary but significantly attenuated the effect of EB. T3 administration also inhibited EB-induced anterior pituitary hyperplasia. D-2 receptor upregulation by EB more likely could reflect a compensatory response to decreased receptor occupation. The present results suggest that D-2 receptors could play an important role in estrogen-induced adenohypophyseal tumor formation and hyperprolactinemia and that thyroid hormones may inhibit estrogen-induced pituitary tumor development via adenohypophyseal D-2 receptors.
Keywords: AMP cyklický; Thyrotropin; Estrogen Antagonists; trijodthyronin; Triiodothyronine; krysa rodu Rattus; Thyroxine; zvířata; prolaktin; Cyclic AMP; receptory dopaminu D2; potkani Wistar; Prolactin; Pituitary Gland, Anterior; Rats, Wistar; Male; adenohypofýza; thyroxin; Rats; Animals; thyreotropin; mužské pohlaví; antagonisté estrogenu; Receptors, Dopamine D2